Peran Zakat dalam Redistribusi Kekayaan dan Penguatan Solidaritas Sosial: Tinjauan Filosofis dan Yuridis - Ahmad Maulana; Lulud Wijayanti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Zakat holds a strategic role as an instrument of wealth redistribution and social solidarity reinforcement in Muslim societies. This study aims to analyze the role of zakat from both philosophical and juridical perspectives in an integrative manner. The research employs a library research method with a conceptual and philosophical-juridical approach. The findings reveal that philosophically, zakat not only transfers wealth from muzaki (payers) to mustahik (recipients) but also purifies the soul of the giver from miserliness and builds collective awareness that the wealth of the rich contains the rights of the poor. Zakat also strengthens social solidarity through the concepts of takaful ijtima'i (social guarantee) and ukhuwah islamiyah (Islamic brotherhood). Juridically, Law Number 23 of 2011 concerning Zakat Management has provided a strong legal foundation for the establishment of BAZNAS and LAZ in Indonesia. However, its implementation still faces various problems such as weak internal supervision, low public transparency, limited human resource capacity, and suboptimal integration between zakat and state fiscal policies. This study recommends the integration of philosophical and juridical approaches in zakat management, along with strengthening professional, transparent, and participatory governance so that zakat can optimally contribute to achieving social justice and communal solidarity